The Effect of Using Behavioral Pain Scale (BPS) by Nurses on Diagnosis of Pain and Relief Care in ICU Patients - Ladan Sedighi; Zhale Mollai; Mehrnaz Ahmadi; meimanat hosseini; Fariba Bolourchifard (Hamadan University of Medical Sciences, 2019)
Introduction: Today, pain is important since it is considered as the fifth vital sign. In patients with decreased consciousness, it is often difficult to detect pain due to the communication barriers. Therefore, this study was conducted to evaluate effect of using Behavioral Pain Scale (BPS) by nurses on diagnosis of Pain and Relief Care in ICU Patients. Methods: This semi-experimental single-group study was conducted with the participation of 68 nurses in the intensive care unit of Hamadan hospitals and selected by census sampling method. The ability to diagnose pain and determine its severity in patients, and pain management methods used by nurses, were evaluated based on the researcher made checklist of evaluation of pain relief before and after the training of behavioral pain monitoring. The collected data were analyzed using SPSS 18. Descriptive statistics were used to determine the frequency, mean, and analytical statistics for comparing ratios and Kolmogorov-Smirnov and Chi-square (P<0.05). Results: The findings showed that after the intervention, the ability to diagnose pain by nurses has optimally changed. The frequency of use of pain relief drug methods increased from 625 to 1222, and the use of non-pharmacological pain relief also increased significantly (P< 0/001). Conclusion: The results of this study indicated that the use of BPS scale has been effective in diagnosing and monitoring pain in patients with decreased consciousness, and has led to optimal changes in the use of non-pharmacological pain relief medications as complementary therapies in intensive care units.